Superman. New Krypton, Volume two. - Gates, Sterling; Robinson, James, 1963-; Johns, Geoff, 1973- (Superman, 2009)
After a long-lost section of Krypton is miraculously resurrected on Earth, The Man of Steel greets thousands of Kryptonians who are suddenly able to walk among humans. But a jarring culture clash destroys relations between the two species and violence erupts! Soon, the government's own anti-Kryptonian team sets out to dispatch the erupting conflict and the entire Superman family is affected! Don't miss this second volume of a 9-part mega-event that alters The Man of Tomorrow down to his core.